Detection of Cadmium and Chromium in some Facial Cosmetics - AL- Azzawi , Muhammed Nafea Ali; AL- Hilifi, Hamsa Tariq Adbl-Razzaq (Iraqi Journal of Science, 2022)
This study was done to compare among 120 new and used cosmetic brands to determine the heavy metals concentrations (Cadmium, Chromium) in (face foundation, powder and blushers). Sixty new cosmetic products were bought from local markets in Baghdad city (twenty different brands foe each cosmetic products), while sixty used cosmetic products were collected from Iraqi women and they had been stored for a long time. This study proved that not all analyzed cosmetic products containing heavy metals concentrations and all concentrations are under Iraqi acceptable limits except one new blusher product which contained chromium with (28 ppm), but all used cosmetic products have shown better results in concentrations of heavy metals than new products and we found that foundations are the best from all analyzed products, although these have emulsion texture which is difficult to store and easily to contaminate; even though most of these cosmetic products have label of ingredients and brand, or free from production and expiration date, that will not prevent any presence of heavy metals within their chemical structure. Women must avoid using the same brand and store the products for a long period to prevent expose to the same chemical ingredients of these products because of being vulnerable to biodegradation and refraining to buy products without a certain brand or country origin.